Disparate Juvenile Court Outcomes for Disabled Delinquent Youth: A Social Work Call to Action - Mallett, Christopher A (2009)
Current service delivery for at-risk youth is through four separate systems: special education; mental health and substance abuse; juvenile justice; and child welfare. Many youth (and their families) are involved with more than one of these systems, making early disability identification and subsequent systems coordination paramount in leading to more successful juvenile court outcomes. This coordination is an important and prioritized public policy concern because a majority of youth (disproportionately minority) within juvenile justice populations has been identified with mental health disorders, special education disabilities, or maltreatment histories. This study of a unique sample of probation-supervised delinquent youths ( n = 397) identifies these disabilities and their corresponding court supervision, detention, and incarceration outcomes for a 48-month period in Cuyahoga County, Ohio (greater Cleveland). Within this youth sample over 32% had a special education disability, over 39% had a mental health disorder, over 32% had a substance abuse disorder, and over 56% were victims of maltreatment. Even higher disability rates were found for those youth who were subsequently detained or incarcerated. Many of these youth had multiple disabilities (and subsequently poorer juvenile court outcomes) and were concurrently involved in more than one disability service system. Policy and client services implications are reviewed and discusse